Faith In God as The Source of Goodness And Religious Moderation In Indonesia: A Christian Moral Perspective - Paskalis Lina; Robertus Wijanarko (International Journal of Indonesian Philosophy & Theology, 2022)
Goodness is the basis and goal of all moral actions. Therefore, ethics, be it theological or philosophical, must in some way explain specifically what goodness is and where one can find it. The Christian faith answers this by stating its fundamental belief that God is good. It says that the Christian belief in goodness is based on faith in God, placing each Christian at the heart of the relationship between faith and moral action. After confirming this fundamental Christian belief that God is the centre of all values, in this paper, we will draw out some implications of the relationship between faith as a personal and communal experience of God and the development of an attitude of religious moderation in a pluralistic Indonesian society. Thus, cultivating an attitude of religious moderation does not stop as an external rule but should go further as an ethical imperative for every Christian.